Effects of Chloroform on the Activity of Na+-K+ Atpase, Catalase, Glutathione and Malondialdehyde Levels in Human Erythrocytes - Gul, Sermin; Bilgin, Ramazan; Tukel, Seyhan (Asian Journal of Chemistry, 2010)
Among all the dyestuff, vat dyes are one of the most popular dyes used on textiles particularly on cotton textile materials. However, vat dye is originally insoluble in water. In conventional vat dyeing process, the vat dye is dissolved using sodium hydrosulphite (hydrose) which is a powerful reducing agent followed by solubilizing with sodium hydroxide. This process creates high pollution problem. Hence, an attempt has been made to see the effect of other reducing agents like ferrous sulphate (2 % owm) and combination of ferrous sulphate with hydrose in various proportions as reducing agent. The results of these reducing agents were compared with those of the vat dyeing with hydrose (2 % owm), in terms of reduction potential of vat dye bath, depth of shade of the fabric and FTIR analysis of vat dye and vat dyed cotton fabric.